Dengue hemorrhagic fever prevention and control: DHF-solve model using linebot-application and GIS - Mala, M.; Meenongwar, C.; Jundaeng, J.; Osman, M.; Viegus, Z.; Nithikathkul, C. (Association for Geoinformation Technology, 2024)
Dengue hemorrhagic fever (DHF) poses a significant health challenge in Thailand, highlighting the need for a better understanding of its transmission and characteristics. Innovation and technology are essential for effective prevention and control measures. This research article centres on developing a model to prevent and control DHF, utilising the DHF-Solve model, a Linebot, and Geographic Information Systems (GIS). The research was conducted in four phases. Phase 1 focused on identifying risk factors and high-risk areas for DHF. Phase 2 examined the factors influencing people's behaviours regarding DHF prevention and control. Phase 3 was dedicated to developing the model, while Phase 4 assessed its effectiveness. The research employed various tools, including GIS, questionnaires, Linebot, assessment forms, and primary and secondary data collection. Risk areas were identified through frequency and weighting techniques as well as descriptive statistical analysis. The factor that most significantly influenced behaviour was people's perception of DHF, which received an average score of 4.19. The findings from the model development indicated that the DHF-Solve Linebot is an effective management and control system for DHF. It features six menus accessible through the Line Official Account (LOA) and can function as a real-time platform. This Linebot incorporates AI chatbot commands and GIS technology, which proved to be the most effective in terms of promptness and responsiveness. It has demonstrated the potential to reduce morbidity rates during two outbreak generations. Therefore, this model effectively addresses the issue of DHF and should be implemented as a response mechanism in emergencies where DHF outbreaks may arise.